Asymmetric Desymmetrization of Oxetanes for the Synthesis of Chiral Tetrahydrothiophenes and Tetrahydroselenophenes. Issue 50 (23rd October 2019) - Zhang, Renwei; Guo, Wengang; Duan, Meng; Houk, K. N.; Sun, Jianwei
Abstract: Chiral tetrahydrothiophenes and tetrahydroselenophenes are highly useful structural units. Described here is a new catalytic asymmetric approach for their synthesis. With a suitable chiral Brønsted acid catalyst, an oxetane desymmetrization by a well‐positioned internal sulfur or selenium nucleophile proceeded efficiently to generate all‐carbon quaternary stereocenters with excellent enantioselectivities. Taming the sulfur and selenium nucleophile in the form of a thioester and selenoester, respectively, is crucial to the success of this work. This approach also allows the facile synthesis of chiral tetrahydrothiopyrans. Mechanistic studies, including DFT calculations, suggested an intramolecular acyl‐transfer pathway. Utilities of the chiral products are also demonstrated. Abstract : Tamed : A new catalytic asymmetric approach for the synthesis of chiral tetrahydrothiophenes and tetrahydroselenophenes bearing all‐carbon quaternary stereocenters is disclosed. This reaction employs a chiral acid to promote efficient desymmetrization of the oxetanes by either a well‐positioned internal sulfur or selenium nucleophile with excellent enantioselectivities. Key to success is the taming of the sulfur and selenium reactivities in the form of a thioester and selenoester, respectively.